2014
DOI: 10.1111/jpn.12234
|View full text |Cite
|
Sign up to set email alerts
|

Dietary supplementation of β‐hydroxy‐β‐methylbutyrate in animals – a review

Abstract: SummaryThe leucine metabolite b-hydroxy-b-methylbutyrate (HMB) has been studied by many researchers over the last two decades. In particular, the utility of HMB supplementation in animals has been shown in numerous studies, which have demonstrated enhanced body weight gain and carcass yield in slaughter animals; positive immunostimulatory effect; decreased mortality; attenuation of sarcopenia in elderly animals; and potential use in pathological conditions such as glucocorticoid-induced muscle loss. The aim of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 56 publications
1
40
0
Order By: Relevance
“…The addition of HMB in human has been associated with beneficial health effects for people suffering from several diseases [28]. In animals, numerous studies have shown that dietary supplementation with HMB improved growth and production performance [29]. In the current study, maternal HMB supplementation during the late gestation had no influence on birth weight of piglets, which is in agreement with previous studies [1,5], although other studies have reported increased birth weight in response to maternal HMB supplementation [12,30].…”
Section: Effects Of Hmb Supplementation On Reproductive Performance Isupporting
confidence: 90%
“…The addition of HMB in human has been associated with beneficial health effects for people suffering from several diseases [28]. In animals, numerous studies have shown that dietary supplementation with HMB improved growth and production performance [29]. In the current study, maternal HMB supplementation during the late gestation had no influence on birth weight of piglets, which is in agreement with previous studies [1,5], although other studies have reported increased birth weight in response to maternal HMB supplementation [12,30].…”
Section: Effects Of Hmb Supplementation On Reproductive Performance Isupporting
confidence: 90%
“…9 Moreover, it reportedly inhibits muscle protein breakdown. 10,11 Some studies have demonstrated the efficacy of HMB on sarcopenia in elderly patients 23 and other clinical conditions in a chronic phase. 24 To date, 3 RCTs of HMB in critical care medicine have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it can inhibit proteolysis in skeletal muscles via proteasome inhibition. 10,11 Three randomized control trials (RCTs) have demonstrated the efficacy of HMB in a critically ill population. [12][13][14] The effectiveness of HMB has been inferred for critically ill patients and for ICU-AW.…”
Section: Introductionmentioning
confidence: 99%
“…71,80 Indeed, a vast number of studies have found that supplementation of HMB to the diet may reverse some of the muscle loss seen in sarcopenia and in hypercatabolic disease. 65,72,83,86,87 The overall treatment of muscle atrophy should include dietary supplementation with HMB, although the optimal dosage for each condition is still under investigation. 68 In addition to dietary protein, EAAs/BCAAs including leucine, the leucine metabolite HMB, a number of other dietary or supplemental components have been explored for their ability to positively influence muscle mass during sarcopenia.…”
Section: Nutritional Strategies For Maintaining and Rebuilding Musclementioning
confidence: 99%